REQUIREMENTS TO THE LIMITATION OF POPULATION EXPO-SURE FROM THE NATIRAL IONIZING IRRADIATION SOURCES IN INDUSTRIAL CONDITIONS - I. P. Stamat; I. K. Romanovich (Радиационная гигиена)
The paper presents conceptually new requirements to the limitation of population exposure from the natural ionizing irradiation sources in industrial conditions, introduced into Basic Sanitary Rules of Radiation Safety (OSPORB-99/2010). It is shown that, first of all, introduction of these requirements is aimed at the resolution of variety of previously existing serious contradictions in organization of radiation safety control and supervision for the impact of natural ionizing irradiation sources in industry.